Directed Search of Anti-inflammatory Agents among (3HQuinazoline-4-ylidene)hydrazides of N-protected Amino acids and their Heterocyclization Products - Martynenko, Yulya Victorivna; Antypenko, Oleksii Mykolayovich; Nosulenko, Inna Stepanovna; Berest, Galina Grigorivna; Kovalenko, Sergii Ivanovich (My University, 2019)
Abstract: Background: (Quinazoline-4-ylidene)hydrazides are valued intermediates in modern organic chemistry, as they are commonly used for the synthesis of substituted [1,2,4]triazolo[1,5-c]quinazolines. Objective: Unknown N-acyl--[1,2,4]triazolo[1,5-]quinazoline-2-yl)-alkyl-(alkaryl-, aryl-)amines were synthesized and evaluated for anti-inflammatory potential. Method: The peculiarities of the synthesized compounds structures were studied by IR-,NMR spectroscopy and chromatography-mass spectrometry and were discussed in detail. Probable molecular mechanisms of activity (inhibition of COX-1 and COX-2) were predicted due to molecular docking. Anti-inflammatory activity of synthesized compounds was determined by their ability to reduce the formalin-induced paw edema in rats. «Diclofenac sodium» was used as reference drug. Results: In this study, the synthesis of N-acetyl-(benzoyl)-2-([1,2,4]triazolo[1,5-c]quinazolinе-2-yl)alkyl-(aralkyl-, aryl-)amines, using (3H-quinazoline--ylidene)hydrazides of Nprotected amino acids or 4-hydrazinoquinazoline and N-prorotected amino acids as starting compounds was developed. It was established that the reaction of (3H-quinazoline-4-ylidene)hydrazides of Boc-amino acids occurred with the formation of N-acetyl-substituted triazoloquinazolines. High anti-inflammatory activity was detected for unknown (3Hquinazoline-4-ylidene)hydrazides Boc-amino acids (1.13-1.15) and N-acetyl-(benzoyl)-2-([1,2,4]triazolo[1,5-c]quinazoline--yl-)aralkyl-(aryl-)amines (3.2, 3.3, 3.11, 3.12), using the experimental «formalin» test. Conclusion: The conducted SAR-analysis allowed to detect «critical» fragments. Namely, the Boc-aminoaralkyl-(aryl-)acid residue in (3H-quinazoline-4-ylidene)hydrazides (1.13-1.15), benzyl and phenyl «linker groups» in N-acetyl-(benzoyl)-2-([1,2,4]triazolo[1,5-c]quinazoline-2-yl-)aralkyl-(aryl-) amines (3.2, 3.3, 3.11, 3.12) are believed to be substantial for anti-inflammatory activity
Keywords: (3H-quinazoline-4-ylidene)hydrazides N-protected amino acids; [1,2,4]triazolo[1,5-c]quinazolines; anti-inflammatory activity; molecular docking; SAR-analysis